Jaringan Ideologi Keilmuan dan Modal Politik Teungku Dayah di Aceh - Nirzalin Nirzalin (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2018)
Teungku Dayah in Aceh is defining community action. The objectivity, their commandment is not only heard with Islamic discourse but also widened in the social and political sphere. Although some social research in Aceh showed the charm of their power had suffered a crisis at the end of the new Order era up to a decade after the new order, but now the vibration of their political influence was again able to move the masses. Based on the study in Bireuen District This article is about to demonstrate that a network of a scientific ideology built, developed and nourished by the constant nurturing by Teungku Dayah has been in apparent political capital for them to A solid and effective mass.